OBTAINING AND IDENTIFICATION OF INULIN FROM JERUSALEM ARTICHOKE (HELIANTHUS TUBEROSUS) TUBERS - Barkhatova T.V. (Foods and Raw Materials, 2015)
The growing demand of the Russian population for healthy food dictates the need in functional ingredients production increase. Inulin, the polysaccharide of natural origin, has a wide range of functional activity. This article grounds the expedience of inulin obtaining from Jerusalem artichoke tubers and considers effective technological methods of ensuring high yield and quality of the target product. It was demonstrated that application of vibration with frequency 24 Hz for 60 min at temperature 30-35°C intensifies the extraction process, and fractionation of the extract on membranes with pore diameter 2, 3 and 5 kDa allows to obtain inulin with certain physicochemical properties. The membrane separation results in three inulin fractions: low molecular (DP=2-10), medium molecular (DP=11-18) and high molecular (DP=19-35) fraction. The medium molecular fraction of inulin, which is used as prebiotic and fat substitute in food technology, was studied using FTIR spectroscopy and 1H-13C NMR spectrometry. The obtained spectral characteristics have led to a conclusion that the investigated sample of inulin is highly competitive with the best world analogues. The authors thoroughly describe the method of determining the degree of polymerization and average molecular weight of the investigated polysaccharide using 1H-13C NMR spectroscopy. It has been established that inulin obtained by improved technology has the degree of polymerization DP = 13-14 and molecular weight 2 124-2 286 Da. The results of this work have practical value for production of inulin from Jerusalem artichoke tubers and theoretical value for the chemistry of natural compounds.